The Structure of the R2TP Complex Defines a Platform for Recruiting Diverse Client Proteins to the HSP90 Molecular Chaperone System - Rivera-Calzada, Angel (Structure, 2017)
The R2TP complex, comprising the Rvb1p-Rvb2p AAA-ATPases, Tah1p, and Pih1p in yeast, is a specialized Hsp90 co-chaperone required for the assembly and maturation of multi-subunit complexes. These include the small nucleolar ribonucleoproteins, RNA polymerase II, and complexes containing phosphatidylinositol-3-kinase-like kinases. The structure and stoichiometry of yeast R2TP and how it couples to Hsp90 are currently unknown. Here, we determine the 3D organization of yeast R2TP using sedimentation velocity analysis and cryo-electron microscopy. The 359-kDa complex comprises one Rvb1p/Rvb2p hetero-hexamer with domains II (DIIs) forming an open basket that accommodates a single copy of Tah1p-Pih1p. Tah1p-Pih1p binding to multiple DII domains regulates Rvb1p/Rvb2p ATPase activity. Using domain dissection and cross-linking mass spectrometry, we identified a unique region of Pih1p that is essential for interaction with Rvb1p/Rvb2p. These data provide a structural basis for understanding how R2TP couples an Hsp90 dimer to a diverse set of client proteins and complexes.